A study on the financial soundness of Bangladesh cement industry using Altman z-score on selected listed companies - Siddika, Sadia Tasnim (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.